1998
DOI: 10.1128/jb.180.11.2875-2882.1998
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of MAE1 , the Saccharomyces cerevisiae Structural Gene Encoding Mitochondrial Malic Enzyme

Abstract: Pyruvate, a precursor for several amino acids, can be synthesized from phosphoenolpyruvate by pyruvate kinase. Nevertheless, pyk1 pyk2 mutants of Saccharomyces cerevisiae devoid of pyruvate kinase activity grew normally on ethanol in defined media, indicating the presence of an alternative route for pyruvate synthesis. A candidate for this role is malic enzyme, which catalyzes the oxidative decarboxylation of malate to pyruvate. Disruption of open reading frame YKL029c, which is homologous to malic enzyme gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(102 citation statements)
references
References 34 publications
8
94
0
Order By: Relevance
“…However, Eqn (9) yields X lb -II(mt-Prv à mt-malate) 0.70. This rather high value is consistent with the observation that malic enzyme gene expression under anaerobic growth is about threefold increased at the transcriptional and about fourfold increased translational level when compared with the aerobic regime [34]. Obviously, the malic enzyme plays a pivotal role for mt-Prv metabolism in both the aerobic and anaerobic regime.…”
Section: Mitochondria: Tca Cycle and Malic Enzyme Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…However, Eqn (9) yields X lb -II(mt-Prv à mt-malate) 0.70. This rather high value is consistent with the observation that malic enzyme gene expression under anaerobic growth is about threefold increased at the transcriptional and about fourfold increased translational level when compared with the aerobic regime [34]. Obviously, the malic enzyme plays a pivotal role for mt-Prv metabolism in both the aerobic and anaerobic regime.…”
Section: Mitochondria: Tca Cycle and Malic Enzyme Activitysupporting
confidence: 90%
“…In S. cerevisiae, this enzyme can involve either NADH or NADPH as a cofactor [33]. The gene encoding the malic enzyme has recently been identified, and the enzyme was shown to be located exclusively in mitochondria [34]. Pyruvate is transported from the cytosol into the mitochondria by the pyruvate (monocarboxylate) carrier protein [35].…”
Section: Oxaloacetate Pyruvate and Acetyl-coamentioning
confidence: 99%
“…The acid enters the cell, being decarboxylated to pyruvate (Rodriguez & Thornton, 1990;Radler, 1993) by the NAD 1 -dependent malic enzyme. Very distinct K m values for malic enzyme have been estimated, 10 mM for S. pombe, 3.2 mM for Z. bailii and 50 mM for S. cerevisiae (Fuck et al, 1973;Kuczynski & Radler, 1982;Viljoen et al, 1994Viljoen et al, , 1999Boles et al, 1998). Pyruvate is then oxidatively decarboxylated to acetaldehyde, which is reduced to ethanol.…”
Section: Krebs-positive Vs Krebs-negative Yeastsmentioning
confidence: 99%
“…In Z. bailii the enzyme seems constitutive [248], while in S. pombe, transcription of the gene mae2 , encoding malic enzyme is induced when cells are grown in high concentrations of glucose or under anaerobic conditions [249]. It has been suggested that this enzyme may play a role in the provision of pyruvate or in maintaining the redox potential under certain conditions [249,250].…”
Section: Gluconeogenesismentioning
confidence: 99%